2021
DOI: 10.1111/jcmm.16394
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of anthropometric indices, rs9939609 FTO gene polymorphism and breast cancer: A case‐control study

Abstract: Contradictory results were reported on the effect of fat mass‐ and obesity‐associated (FTO) gene and anthropometric measurements on breast cancer (BC). This study aimed to assess the interactions between rs9939609 polymorphism of FTO gene, anthropometric indices and BC risk in Iranian women. This case‐control study was performed on 540 women including 180 women with BC and 360 healthy women in Tehran, Iran. Physical activity and dietary intakes were assessed by validated questionnaires. Data on sociodemographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…It has been observed that the association between the rs9939609 SNP and MetS is higher in subjects with a low level of physical activity [65]. However, evidence shows that performing physical activity can significantly attenuate the rs9939609 SNP of the FTO gene [66][67][68] and other genes associated with obesity and metabolic alterations [69].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the association between the rs9939609 SNP and MetS is higher in subjects with a low level of physical activity [65]. However, evidence shows that performing physical activity can significantly attenuate the rs9939609 SNP of the FTO gene [66][67][68] and other genes associated with obesity and metabolic alterations [69].…”
Section: Discussionmentioning
confidence: 99%
“… 25 A recent case‐control study by Doaei et al, found no significant relationship between BC and the risk allele (A) of FTO rs9939609 in participants with normal BMI. 26 in contrast with Zhao et al indicating the association of FTO rs9939609 with BC risk. 27 Mozaffarizadeh et al reported that rs9939609 FTO gene polymorphism was significantly associated with BC risk in overweight individuals.…”
Section: Discussionmentioning
confidence: 65%
“…A case–control study was conducted on 180 patients with cancer as the case group and 360 healthy individuals as the control group. The required sample size was estimated based on the odds ratio (OR) of the previous studies 31 . According to inclusion criteria, the participants were selected among women referred to the Cancer Research Center of Shohadaye Tajrish Hospital in Tehran, Iran.…”
Section: Methodsmentioning
confidence: 99%
“…The required sample size was estimated based on the odds ratio (OR) of the previous studies. 31 According to inclusion criteria, the participants were selected among women referred to the Cancer Research Center of Shohadaye Tajrish Hospital in Tehran, Iran. Individuals whose blood samples were collected at the beginning of the study were eligible to participate in the study according to the inclusion and exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%